Notes about the studies of the guidance process between supervisor and advisee: from university models to a dialogic reflection in stricto sensu Brazilian postgraduate studies in the context of the Professional Master’s Degree (PROFLetras): de los modelos universitarios a una reflexión dialógica en los programas de posgrado stricto sensu brasileños en el contexto de la Maestría Profesional (PROFLethras) (Olhar de Professor, 2022)
This article has as objective to present a part of a research already concluded that has as general aim to investigate, in the light of a dialogical perspective of discourse, the process of verbal interaction between supervisor and advisee in the professional master’s contexto (PM) (PROFLetras), of a brasilian public university. In this text, the part of the literature review is presented, from the concepts of university, highlighting the one that underlies the creation of Brasilian postgraduate studies and reaching notes that deal with such an orientation process under the aegis of research already carried out in special in the field of academic postgraduation and in the education area. In other moment, we propose a concept to what can be understood as academic orientation – in a Bakhtinian vein. The preliminary results point to the need of understand the protagonism of these social subjects – supervisor and advisee – in the context of the PM, which is where the basic education teacher is developing his applied research.
Keywords: Supervisor-advisee relation.; PROFLetras.; Bakhtin’s Circle.